Development and characterization of the ECLIPS space environments simulation facility. (May 2022) - Wilson, Kieran; Romero-Calvo, Álvaro; Bengtson, Miles; Hammerl, Julian; Maxwell, Jordan; Schaub, Hanspeter
Abstract: The Electrostatic Charging Laboratory for Interactions between Plasma and Spacecraft (ECLIPS) research vacuum chamber has recently been developed as part of the Autonomous Vehicle Systems Laboratory at the University of Colorado Boulder. The experimental spacecraft charging research facility allows conducting experiments relevant to charged astrodynamics in a space-like environment. This paper discusses the development, characterization, and present capabilities of the vacuum chamber, which includes a range of sources to provide electron, ion, and photon fluxes, probes to characterize electron fluxes, x-rays, and potentials, and a variety of ancillary components to ensure the safe operation of the system, such as 3-axis motion stages, a magnetic environment control system, or a residual gas analyzer, among others. This state-of-the art facility has been used to conduct experiments on touchless spacecraft potential sensing, electrostatic actuation, or electron gun development, and will continue to be employed for the study of charged astrodynamics in the future. Highlights: ECLIPS is a vacuum chamber facility designed to study charged astrodynamics experimentally. The motivation, design, and characterization of ECLIPS are presented. Applications include research relevant to the electrostatic tractor concept or touchless spacecraft potential sensing.